PENERAPAN MODEL INKUIRI TERBIMBING INTEGRASI PEER INTRUCTION UNTUK MENINGKATKAN KETERAMPILAN BERARGUMENTASI SISWA MATERI GETARAN DAN GELOMBANG KELAS VIII SMPN 3 PEKANBARU - Nova Julianti; Azhar Azhar; Muhammad Nasir (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research aimed to determine the differences of students argumentation skills the Peer Instruction Integrated Guided Inquiry Learning model and conventional learning on physics material vibration and wave of class VIII material in SMPN 3 Pekanbaru. The kind of research use is quasi-experimental with Posttest Only Control Design. The subject of study is learners class VIII SMPN 3 Pekanbaru academic year 2018 /2019, consisting of class VIII.5 as a class the experiments were 36 students and class VIII.4 as a class control by 36 students. Research instruments used is about a test argumentation skills. Engineering data collection in this research by giving a test argumentation skills after learning held on second class. The Data is analysed in descriptive to see the results of the percentage on argumentation skills and analysed in inferential using the Ttest. The result showed that there are significant differences between argumentation skills of students on a peer instruction integrated guided inquiry learning model applies with class conventional who apply the vibration and waves to the matter argumentation skills of class experiment score of average higher than class control. Based on the research so that it can be concluded that peer instruction integrated guided inquiry learning model to argumentation skills of students to the matter the sound waves class VIII SMPN 3 Pekanbaru.Key Words:Argumentation Skills,Peer Instruction, Guided Inquiry,Vibration and Wave.